Sınıf Öğretmenlerinin Öğretmen Yeterlik ve Öğretmen Liderlik Düzeylerinin Değerlendirilmesi - Ağırman, Nesibe; Ercoşkun, Muhammet Hanifi (Muş Alparslan Üniversitesi, 2017)
The aim of this study is to evaluate the level of teacher efficiency and teacher leadership, determine the relationship between views on teacher qualification and expectations and perceptions of teacher leadership roles, identify the predictive situation of expectations and perceptions of views on teacher qualification related to teacher leadership roles. In this study, the relational survey of descriptive research model which is a qualitative research method was used. Data collection tools are Teacher Efficacy Scale and Teacher Leadership Scale. As a result of study, it has been found that the level of teacher efficiency of classroom teachers is midlevel; the level of teacher leadership is high level. A low level positive relationship between classroom teachers'expectations and perceptions of views on teacher qualification related to teacher leadership roles has also been detected. It has been precipitated that classroom teachers'views on teacher qualification is low level predictor of expectations and perceptions of teacher leadership roles.

Bu çalışmada sınıf öğretmenlerinin, öğretmen yeterlik ve öğretmen liderlik düzeylerinin değerlendirilmesi, öğretmen yeterliğine ilişkin görüşleri ile öğretmen liderlik rollerine ilişkin beklenti ve algıları arasındaki ilişkinin belirlenmesi, öğretmen yeterliğine ilişkin görüşlerinin öğretmen liderlik rollerine ilişkin beklenti ve algılarını yordama durumunun belirlenmesi amaçlanmıştır. Bu araştırmada nicel araştırma yöntemi olan betimsel tarama modellerinden ilişkisel tarama modeli kullanılmıştır. Veri toplama aracı olarak Öğretmen Yeterlik Ölçeği (Diken, 2004)  ve Öğretmen Liderlik Ölçeği (Beycioğlu ve Aslan, 2010)  kullanılmıştır. Araştırma sonucunda, sınıf öğretmenlerinin öğretmen yeterlik düzeylerinin orta; öğretmen liderlik düzeylerinin yüksek olduğu bulunmuştur. Sınıf öğretmenlerinin öğretmen yeterliklerine ilişkin görüşleri ve öğretmen liderlik rollerine ilişkin beklenti ve algıları arasında düşük düzeyde pozitif bir ilişki olduğu saptanmıştır. Sınıf öğretmenlerinin öğretmen yeterliklerine ilişkin görüşlerinin, öğretmen liderlik rollerine ilişkin beklenti ve algılarının, düşük düzeyde anlamlı bir yordayıcısı olduğu sonucuna ulaşmıştır.
Evaluation of Class Teachers'Level of Teacher Efficiency and Teacher Leadership
anemon
Keywords: Classroom Teacher; Teacher Efficiency; Teacher Leadership; Sınıf Öğretmeni; Öğretmen Yeterliği; Öğretmen Liderliği